Chapter Ограничительные факторы синтаксических трансформаций русских идиом - Gasanova Mijat, Marina (Biblioteca di Studi Slavistici, 2016)
This paper attempts to identify the factors that either limit the passivization and decausation of Russian idioms containing transitive verbs of movement. Most of these verbs are highly subject to passivization in free structures and produce causative-decausative pairs. But in phraseological units their transformation is not always possible. The purpose of this research is to reveal the semantic and grammatical features that restrict the above transformations, to identify their primary or auxiliary role and to determine the existence of common features that resist both types of transformation.